Validation and extension of the METSSS score in a metastatic cancer patient cohort after palliative radiotherapy within the last phase of life. (May 2022) - Christ, Sebastian M.; Schettle, Markus; Willmann, Jonas; Ahmadsei, Maiwand; Seiler, Annina; Blum, David; Guckenberger, Matthias; Andratschke, Nicolaus; Hertler, Caroline
Highlights: Predictive tools are intended to improve decision-making and personalize treatment. The "METSSS score" was proposed to predict survival after palliative radiotherapy. An extension of the "METSSS score" to radiotherapy during end-of-life proved valid. To assess the real quality of the tool, its routine use in clinical practice is encouraged. Abstract: Introduction and background: Choosing the right treatment for the right patient in a setting of metastatic cancer disease remains a challenge. To facilitate clinical decision-making, predictive tools have been developed to personalize treatment. Here, we aim to assess the use of the recently proposed "METSSS score" as a prognostic tool for overall survival of cancer patients after palliative radiotherapy in the last phase of life. Methods: All patients treated with palliative radiotherapy at the end-of-life at the Department of Radiation Oncology of the University Hospital Zurich between January 2010 and December 2019 were included in this study. Data on demographics, diagnosis, treatment and comorbidities was extracted from the treatment planning and the electronical medical records system. To statistically assess the validity of the "METSSS score", the mortality risk score was calculated, followed by stratification of all patients to prognostic risk groups. The prediction of the 1-year overall survival estimates was subsequently calculated. Results: Over the past decade, 274 patients have received palliative radiotherapy during the end-of-life period. One third of patients was female (34%, n = 93). The most frequent primary tumor was lung cancer (n = 121, 44%), and 55% of patients (n = 152) had no comorbidities according to the Charlson-Deyo comorbidity index. The most common radiotherapy site was the brain and eye region (42%, n = 115). The median actual overall survival of all patients was 40 days from the start of radiotherapy. The "METSSS score" survival model predicted that 269 patients (98.1%) belong into the high-risk, four patients (1.5%) into the medium-risk, and one patient (0.4%) into the low-risk group. The predicted median 1-year overall survival was 10%. Discussion: The METSSS score correctly predicted the survival of our end-of-life patient cohort by assigning them into the highest risk category, and it can therefore serve as a decision-making tool when assigning patient to symptomatic radiotherapy.